Potassium Current Signature of Neuronal/Glial Progenitors in Amniotic Fluid Stem Cells - Paola Sabbatini; Sabrina Cipriani; Andrea Biagini; Luana Sallicandro; Cataldo Arcuri; Rita Romani; Paolo Prontera; Alessandra Mirarchi; Rosaria Gentile; Diletta Del Bianco; Elko Gliozheni; Sandro Gerli; et al. (Cells)
Amniotic fluid is a complex and dynamic biological matrix that surrounds the fetus during the pregnancy. From this fluid, is possible to isolate various cell types with particular interest directed towards stem cells (AF-SCs). These cells are highly appealing due to their numerous potential applications in the field of regenerative medicine for tissues and organs as well as for treating conditions such as traumatic or ischemic injuries to the nervous system, myocardial infarction, or cancer. AF-SCs, when subcultured in the presence of basic Fibroblast Growth Factor (bFGF), have been shown to survive and migrate when transplanted into the striatum of the rat brain, exhibiting behavior characteristics of neuronal/glial progenitor cells. In this work, we performed an electrophysiological characterization to ascertain the propensity of AF-SCs to differentiate into glial and neuronal cells by bFGF. By using patch clamp technique we characterized a fibroblast-like morphology that display a barium-sensitive inward-rectifying potassium current (Kir) and calcium-activated potassium currents (KCa). The electrophysiological and calcium dynamics of histamine, a marker of undifferentiated neural progenitors, was further studied. Histamine promoted intracellular calcium increase by Fura-2 recording and calcium-activated potassium current activation with a similar temporal profile in AF-SC. The data presented in this paper ultimately confirm the expression in AF-SCs of the Kir and KCa currents, also showing regulation by endogenous stimuli such as histamine for the latter.